A Bibliometric Evaluation of Green Finance and Green Innovation: Research Trends and Future Directions (Journal of Asian Development Studies, 2023)
Green finance innovation is of essential importance in relation to the development of financial execution ingrained with constructive environmental influences. The change in climate is evidently a major issue which is being faced for foreseeability of the future. Many research articles emphasize emerging trends in association with publishing work attributed to innovations in green finance. This research article scrutinizes thorough evaluation using bibliometric analysis to shed light on the existing landscape and emerging trends in sustainable and green finance. Scopus database is used to collect data on the literature on green innovative finance and green innovation. To analyze the data, this study employed various software programs such as MS Excel and VOS viewer. The findings of this investigation indicate that the finance literature has grown substantially. However, this growth is mainly concentrated in China due to favorable conditions for research in this area. Based on the top 10 journals categorized as A/A* by ABDC, there was a noticeable increase in publications appertaining to green finance innovation in China and the UK. Professor Zhang Dongyang of the Capital University of Economics & Business Beijing, China, is the leading author with 181 publications based on the top 10 journals categorized as A/A* by ABDC. This study presents the latest information on the present state of green finance and innovation globally.